Association and Path Coefficient Analysis of Grain Yield and Its Attributing Traits in Different Genotypes of Wheat (Triticum aestivum L.) - Kandel, Manoj; Bastola, Arjun; Sapkota, Pradeep; Chaudhary, Omprakash; Dhakal, Pratiksha; Chalise, Pushpa (International Journal of Applied Sciences and Biotechnology, 2017)
Forty-one wheat genotypes were tested in randomized complete block design with three replications at experimental farm of Institute of Agriculture and Animal Science Paklihawa, Rupendehi, Nepal in 2014 spring season. The objective of this study was undertaken to estimate the correlation and path coefficient of yield and its contributing traits The data showed that the grain yield had significant associated with biomass and significant correlation with number of effective tillers (0.36*), thousand grain weight (0.376*) and harvest index (0.37*). Path coefficient analysis revealed maximum positive direct contribution towards yield by biomass (0.94) and harvest index (0.3).The study suggested that these traits may serve as effective selection attributes during breeding program for yield improvement in wheat. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 449-453.